Urinary Function following Laparoscopic Lymphadenectomy for Male Rectal Cancer - Liu, Li-ye; Liu, Wei-hui; Cao, Yong-kuan; Zhang, Lin; Wang, Pei-hong; Tang, Li-jun (PLOS ONE, 2013)
Objectives Urinary function can be protected following open lateral node dissection (LND) with pelvic autonomic nerve preservation (PANP) for advanced rectal cancer. However data regarding urinary function after laparoscopic LND with PANP have not been reported. The goal of this study was to determine the effects of laparoscopic LND with PANP on urinary function in male patients with rectal cancer. Methods Urine flowmetry was performed using an Urodyn flowmeter. Patients were also asked to complete the standardized International Prostate Symptom Score (IPSS) questionnaire before surgery and 6 months after. In total, this study consisted of 60 males with advanced rectal cancer. Results No significant differences were seen in maximal urinary flow rate, voided volume or residual volume before and after surgery. The total IPSS score increased significantly after surgery and at least 41 patients (68.3%) reported there was no change in one of the seven IPSS questions. Conclusions Laparoscopic LND with PANP was relatively safe in preserving urinary function.